Глобальные вызовы политической стабильности: ХХІ век - Нечаева-Юрийчук, Наталия (My University, 2021)
This article is dedicated to the global challenges of our time, among which, according to the author, the main place belongs to the informational ones. The rapid development of information and communication technologies, the digitization processes of all spheres of life have led to the transformation of relations both in the domestic political arena of the states and in the international one. The revolutionary events in Ukraine have become a kind of catalyst for a change in the architecture of the world order, and the COVID-19 pandemic has contributed to the adoption of new approaches in the field of information and communication
Keywords: security challenges, digitization, information and communication technologies, COVID-19 / вызовы безопасности, диджитализация, информационно- коммуникационные технологии, COVID-19